Microstructure and Properties of Bulk Ultrafine-Grained Cu1.5Cr0.1Si Alloy through ECAP by Route C and Aging Treatment - Tingbiao Guo; Xiaoyang Tai; Shiru Wei; Junjie Wang; Zhi Jia; Yutian Ding (Crystals, 2020)
The evolutions of the microstructure and its effect on the mechanical and electrical conductivity properties of Cu1.5Cr0.1Si alloy after equal channel angle pressing (ECAP)-C path deformation and aging treatment have been investigated using scanning electron microscopy (SEM), x-ray diffraction (XRD), and electron back-scattered diffraction (EBSD). It was found that after the ECAP-C deformation at room temperature, with an extension of aging time, the strong (111) macro orientation formed in the Cu1.5Cr0.1Si alloy. The ultrafine crystals formed by ECAP and the rich chromium phase precipitated along grain boundaries during the aging process greatly improved the material strength. After aging at 350 °C for 4 h, the tensile strength, elongation, and conductivity reached 528 MPa, 15.27%, and 78.9% IACS, respectively. The fracture mode of the alloy was ductile fracture. The steady-oriented {111} <110> texture was beneficial to improving the conductivity of the material.